Tingkat kecemasan, asupan makan, dan status gizi pada lansia di Kota Yogyakarta - Ninna Rohmawati; Ahmad Husein Asdie; Susetyowati Susetyowati (Jurnal Gizi Klinik Indonesia, 2015)
Background: Psychological factors such as anxiety have significant contributions in determining dietary intake and nutritional status of elderly. Prevalence of malnutrition in elderly has achieved significant level.Objective: To determine the correlation between anxiety level with dietary intake and nutritional status of elderly in Yogyakarta municipality.Method: This research was observational with cross sectional design. Subjects were elderly in Yogyakarta municipality who fulfilled inclusion criteria. Research subjects consisted of 214 people. Anxiety level was measured with trait-manifest anxiety scale (T-MAS) form, dietary intake with semi-quantitative food frequency questionnaire (SQFFQ) method, and nutritional status was determined based on body mass arm span (BMA). Data were analyzed with Chi-Square test and multiple logistic regression.Results: A percentage of 26.2% subjects had moderate anxiety level. Most dominant factors that influenced anxiety level was sex (OR=3.37). Bivariate analysis showed a significant correlation between anxiety level and nutritional status (p<0.05), subjects with moderate anxiety level were more likely to have higher nutritional status (OR=3.54) and lower nutritional status (OR=2.29). Significant correlation was found between moderate anxiety level with excessive dietary intake (p<0.001; OR=6.22). Significant correlation was also found between dietary intake with nutritional status (p<0.05), subjects with excessive dietary intake were more likely to have higher nutritional status (OR=6.15).Conclusion: Significant correlation was found between anxiety level and nutritional status. Significant correlation was also found between anxiety level and dietary intake, and significant correlation was found between dietary intake and nutritional status.